Draft 11th Five Year Plan 2007-12 and Annual Plan 2007-2008 U.T. of Daman and Diu - Planning Commission (Planning Commission, 2007)
The district of Daman is known to have formed part of the country known as Lata which was one of the seven divisions of the Apparent or Konkan Vishaya, between 2nd Century B.C. to 13th Century A.D. The Daman District is included in the intervening region and therefore must have formed part of the Mauryan empire at least at the time of Ashoka. After the Mauryan power was weakened, the district was under the rule of Satkami I, the Satavahana ruler in the end of 2nd Century B.C. After that during the 1st Century A.D. the district of Daman seemed to have been ruled by Kshaharatas who were the provincial governors i.e. Kshatrapas under the Kushana emperors.
Department of Planning and Statistics